Myths of Canadian Identity in Oil Sands Industry Advertisements. A semiotic analysis of the Canadian Association of Petroleum Producer’s Raise Your Hand campaign - Cantin, Amélie (Université d'Ottawa | University of Ottawa, 2017)
The issue of bitumen sands in Alberta has raised more than a few eyebrows, some with excitement and others with disapproval. Canadian citizens are bombarded by the media with images and slogans that attempt to convince them to adopt a position on the subject. The intent of this study is to examine how a lobby group uses elements of national identity to create a social movement in support of the Alberta bitumen industry. In applying Barthes’ semiotic theory to advertisements, the present study finds a seemingly natural rhetoric, described as myths, in the messaging presented by the Canadian Association of Petroleum Producers (CAPP) in their Raise Your Hand advertising campaign. The semiotic analysis of the campaign uncovered four prominent myths; positivity, responsibility, balance and pride. These myths harbour CAPP ideologies and are published in a way that utilises ideas that seem natural in society.